Pengaruh Level Soy Milk Waste (SMW) Terhadap Produktivitas Ayam Pejantan Buras - Haryuni, Nining; Khopsoh, Binti (BRILIANT: Jurnal Riset dan Konseptual, 2024)
This biological research aims to obtain the best level of soy milk waste (SMW) in improving the productivity of native chicken roosters. The object of this biological research is 20 native chicken roosters aged 85 weeks with chicken weights ranging from 2.70 – 3.0 kg in healthy condition. The design used in this biological test was a completely randomized design (CRD) with 5 SMW levels and repeated 4 times for each level. Statistical analysis shows that SMW as an alternative feed ingredient for male free-range chickens has a very significant effect (P<0.01) in reducing feed consumption and increasing semen production but has no significant effect (p>0.05) on mortality and Rooster weight gain. The average consumption of native chicken roosters from 107.50 - 118.17 g/bird/day; mortality 0.00%; PBB 19.11- 20.89 g/head/day; cement production 0.73- 1.19 ml. The results obtained from biological tests on native chicken roosters can be concluded that the use of soy milk waste (SMW) can improve the productivity of native chicken roosters. The best level of SMW use in improving the productivity of native chicken roosters is 15%.